First observation of the anomalous electric field in the topside ionosphere by ionospheric modification over EISCAT. Issue 21 (12th November 2014) - Kosch, M. J.; Vickers, H.; Ogawa, Y.; Senior, A.; Blagoveshchenskaya, N.
Abstract We have developed an active ground‐based technique to estimate the steady state field‐aligned anomalous electric field (E*) in the topside ionosphere, up to ~600 km, using the European Incoherent Scatter (EISCAT) ionospheric modification facility and UHF incoherent scatter radar. When pumping the ionosphere with high‐power high‐frequency radio waves, the F region electron temperature is significantly raised, increasing the plasma pressure gradient in the topside ionosphere, resulting in ion upflow along the magnetic field line. We estimate E* using a modified ion momentum equation and the Mass Spectrometer Incoherent Scatter model. From an experiment on 23 October 2013, E* points downward with an average amplitude of ~1.6 μV/m, becoming weaker at higher altitudes. The mechanism for anomalous resistivity is thought to be low‐frequency ion acoustic waves generated by the pump‐induced flux of suprathermal electrons. These high‐energy electrons are produced near the pump wave reflection altitude by plasma resonance and also result in observed artificially induced optical emissions.